CONTINUITY AS ACMEOLOGICAL CATEGORY IN THE CONTEXT OF FORMATION OF PROFESSIONAL AND CREATIVE ABILITIES OF FUTURE ENGINEERS - Alla G. Mikhailova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The author explores one of the most urgent problems of modern education - features of for-mation of professional and creative abilities of future engineers in the context of ensuring continuity in education in the current socio - economic situation of the Crimea. The author stresses the particular relevance of the identity formation of the future engineer with professional and creative abilities in the context of the existing gap between education and production. Acmeological approach to form a system of continuity education is proposed. The main teaching methods for future engineer’s professional and creative abilities formation in the process of professional education are analyzed.